Greater muscle protein synthesis and mitochondrial biogenesis in males compared with females during sprint interval training. Issue 6 (5th March 2014) - Scalzo, Rebecca L.; Peltonen, Garrett L.; Binns, Scott E.; Shankaran, Mahalakshmi; Giordano, Gregory R.; Hartley, Dylan A.; Klochak, Anna L.; Lonac, Mark C.; Paris, Hunter L. R.; Szallar, Steve E.; Wood, Lacey M.; Peelor, Frederick F.; et al.
ABSTRACT: Improved endurance exercise performance in adult humans after sprint interval training (SIT) has been attributed to mitochondrial biogenesis. However, muscle protein synthesis (MPS) and mitochondrial biogenesis during SIT have not been measured, nor have sex‐specific differences. We hypothesized that males and females would have similar rates of MPS, mitochondrial biogenesis, and synthesis of individual proteins during SIT. Deuterium oxide (D2 O) was orally administered to 21 adults [11 male, 10 female; mean age, 23±1 yr; body mass index (BMI), 22.8±0.6 kg/m 2 ; mean± se ] for 4 wk, to measure protein synthesis rates while completing 9 sessions of 4–8 bouts of 30 s duration on a cycle ergometer separated by 4 min of active recovery. Samples of the vastus lateralis were taken before and 48 h after SIT. SIT increased maximum oxygen uptake ( V O2max, males 43.4±2.1–44.0±2.3; females 39.5±0.9–42.5±1.3 ml/kg/min; P =0.002). MPS was greater in the males than in the females in the mixed (~150%; P < 0.001), cytosolic (~135%; P =0.038), and mitochondrial (~135%; P =0.056) fractions. The corresponding ontological clusters of individual proteins were significantly greater in the males than in the females (all P <0.00001). For the first time, we document greater MPS and mitochondrial biogenesis during SIT in males than in females and describe the synthetic response of individual proteins in humans during exercise training.—Scalzo, R. L., Peltonen, G. L., Binns, S. E., Shankaran, M., Giordano, G. R., Hartley, D. A., Klochak, A. L., Lonac, M. C., Paris, H. L. R., Szallar, S. E., Wood, L. M., Peelor, F. F., III, Holmes, W. E., Hellerstein, M. K., Bell, C., Hamilton, K. L., Miller, B. F. Greater muscle protein synthesis and mitochondrial biogenesis in males than in females during sprint interval training. FASEB J . 28, 2705–2714 (2014). www.fasebj.org